Peningkatan Manfaat Buah Rotan Manau (Calamus Manan Miq.) Berdasarkan Potensi Bioaktivitas - Daud Salusu, Heriad; Aryani, Farida; Budiarso, Edy; Wijaya Kusuma, Irawan; Tangke Arung, Enos (Jurnal Ilmiah Inovasi, 2018)
Rattan manau (Calamus manan Miq.) is one of the many commercial rattan species grown in the forests of East Kalimantan. The fruit can be eaten as well as the fruits of some other types of rattan, but it is also traditionally used by locals as stomach ache or toothache. Until now there has been no research that investigates the benefits of fruit for medicinal purposes or other benefits. This study aims to determine the bioactivity potential contained in the fruit of Calamus manan Miq. including phytochemical content, antioxidant properties, toxicity properties, and antibacterial activity. Parts of fruit, pericarp, flesh and seed are tested using ethanol as a solvent. The results of study showed that the pericarp and seed have higher antioxidant activity than fruit flesh where the seed have IC50 value 25,04 ppm, pericarp 41,17 ppm and fruit flesh 170,19 ppm; based on toxicity properties using BSLT (Brine Shrimp Lethality Test) test of rattan manau fruit is not toxic; while antibacterial activity against two types of bacteria showed pericarp and seeds are antibacterial activity against to Escherichia coli with strong category, while antibacterial activity against Streptococcus mutans is weak category. Keywords: antioxidant, toxicity, antibacterial, rattan, calamus.